Assessment of Cartilage Growth After Biopsy of Osteochondral Loose Bodies in Adolescent Knees for Use in Autologous Chondrocyte Implantation. Issue 3 (March 2020) - Robinson, Sean; Kramer, Jonathan; Shelton, Trevor; Merriman, Jarrad; Haus, Brian
Abstract : Background: The goal of this study is to determine whether harvested cartilage from an osteochondral loose body maintains the same viability for implantation as cartilage harvested from the traditional locations within the adolescent knee for autologous chondrocyte implantation (ACI). Methods: A retrospective study was performed on all ACI procedures performed from 2014 to 2017 at a single institution. Biopsies were derived from 2 groups: osteochondral loose body verses the intercondylar notch. The viability, yield, identity, potency, and density were obtained from each sample in addition to basic demographics and concomitant injuries. A total of 12 patients with osteochondral loose bodies 14.6 (SD=2.9) and 20 patients 13.6 (SD=3.3) with intercondylar notch biopsies were evaluated for the study. Results: In the microscopic and histologic comparison, there was no significant difference in viability: 94% in the loose bodies and 93% in the intercondylar notch groups, identity: 7.4 d5L versus 6.3 d5L, or yield. Minimum yield is presented as different units in Carticel (1.2×10 7 cells/vial) and matrix-induced ACI (>8500 relative fluorescent units) products; however, there was no difference between groups and all samples were above the acceptable limit. Minimum identity value is recorded as d5L> −2.00 and all samples were above this limit. In addition, no sample had signs of contamination or endotoxin in either group. Conclusion: These results demonstrate an alternative method for obtaining cartilage biopsies in ACI procedures that may limit short-term and long-term donor site morbidity. Level of Evidence: Level III.